Proceedings of the Vertical Flight Society 76th Annual Forum 2020
DOI: 10.4050/f-0076-2020-16489
|View full text |Cite
|
Sign up to set email alerts
|

Rotor-on-Rotor Aeroacoustic Interactions of Multirotor in Hover

Abstract: Multirotor configurations introduce complicated aerodynamic and aeroacoustic interactions that must be considered during aircraft design. In this paper we explore two numerical methods to model the acoustic noise caused by aerodynamic rotor-on-rotor interactions of rotors in hover. The first method uses a conventional mesh-based unsteady Reynolds-average Navier-Stokes (URANS) solver, while the second consists of a meshless Lagrangian solver based on the viscous vortex particle method (VPM). Both methods are co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Studies in the literature involving multiple propellers have mainly focused on the hover condition. It is shown that proximity between propellers causes, depending on configuration, a detrimental effect on thrust generation, corresponding to a loss of up to 8% [9,10]. The higher percentages appear especially for hovering conditions.…”
Section: Introductionmentioning
confidence: 98%
“…Studies in the literature involving multiple propellers have mainly focused on the hover condition. It is shown that proximity between propellers causes, depending on configuration, a detrimental effect on thrust generation, corresponding to a loss of up to 8% [9,10]. The higher percentages appear especially for hovering conditions.…”
Section: Introductionmentioning
confidence: 98%